2023
DOI: 10.3390/toxics11020161
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Understanding of Adsorption Behaviors of Legacy and Emerging Per- and Polyfluoroalkyl Substances (PFASs) on Various Anion-Exchange Resins

Abstract: Per- and polyfluoroalkyl substances (PFASs) have received extensive attention due to their various harmful effects. In this study, the adsorptive removal of 10 legacy and emerging PFASs by four anion-exchange resins (including gel and macroreticular resins) were systematically investigated. Our results showed that the capacities of resins absorbing PFASs were ranked in the following order: gel strong base HPR4700 (297~300 μg/g) ≈ macroreticular strong base S6368 (294~300 μg/g) ≈ macroreticular weak base A111S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…29 Associations differed by specific PFAS but were most consistent for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA). 29 All but one of the previous studies were conducted in Scandinavian countries. The sole US study was conducted in a population having higher serum PFOA concentrations relative to the general US population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Associations differed by specific PFAS but were most consistent for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA). 29 All but one of the previous studies were conducted in Scandinavian countries. The sole US study was conducted in a population having higher serum PFOA concentrations relative to the general US population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined associations between pregnancy PFAS concentrations and breastfeeding duration. 7,23–29 In a recent systematic review of the six previous epidemiologic studies on this topic, five of the six found higher PFAS concentrations were associated with shorter breastfeeding duration. 29 Associations differed by specific PFAS but were most consistent for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the commercial ion-exchange resins studied in PFAS removal include IRA67, IRA910, Amb IRA400, PFA300, PFA400, PFA444, A520E, A600E, A500p, A860, and A532E [1,7,16]. Scientific research shows various ion exchange resins (HPR4700, S6368, and A111S) as of high interest in PFAS removal by adsorption techniques [17]. There have also been a few reports on using magnetic ion exchange (MIEX) resin that was produced by Orica Watercare and IXOM Australia (MIEX ® DOC resin) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The biosorbents present several advantages in comparison to traditional adsorbents, such as they are produced by simple and low-cost processes, they have high efficiency, and they are ease to use and environmentally friendly. Whereas the traditional synthetic adsorbents are mainly manufactured from non-biosourced materials, such as synthetic polymers 33 35 , ion exchange resins 36 , 37 and activated carbon 38 40 ; this means that they are not biodegradable. Their production consumes great amounts of raw materials and energy and can generate toxic by-products and have net negative environmental fingerprint.…”
Section: Introductionmentioning
confidence: 99%